Essentials of differential diagnosis a book for medical students and young doctors - Inayatullah, Muhammad; Nasir, Shabbir Ahmed (Paramount Publishing Enterprise, 2013)
There are no shortcuts in Medicine but this book is designed to make the study uncomplicated. Easy to study and comprehend, Essentials of Differential Diagnosis is an aid to one of the facets of Medicine. It not only provides the list of cuases for a particular symptom but also contain ample discussionon diseases.